The Proposed Twenty-Seventh Amendment: A Brief, Supportive Comment - William W. Van Alstyne (Washington University Law Quarterly, 1979)
I have come to believe that approval of the proposed twenty-seventh amendment provides the most appropriate answer to the same questions that were deemed sufficient to justify ratification of the earlier and equally important amendments that constitute our Bill of Rights. Those questions I think to be these three. First, is the subject of the amendment of sufficient importance to warrant recognition in the Constitution of the United States? Second, is the particular subject inadequately addressed in the Constitution? And third, does the manner in which the subject is treated in this amendment fairly compare with the essential style of the Bill of Rights itself?
Keywords: Constitutional amendments; Sex discrimination; Equal protection; Equal Rights Amendment